DFT Investigations of BeSnN2 Chalcopyrite Compound for Optoelectronic Applications. Issue 1 (1st February 2022) - Lathwal, Sanjay; Gaur, Aditi; Khan, Karina; Goyal, Sunil Kumar; Soni, Amit; Sahariya, Jagrati
Abstract: The ternary chalcopyrite compounds are a very renowned category to perform the theoretical investigation in order to find out a proper and apt compound for optoelectronic application. Solar cell is a very interesting field to compensate the energy supplying needs in place of other electricity generating sources. Several semiconductor compounds have been investigated and amongst them we have done a theoretical investigation of pure BeSnN2 using DFT based computational tool i.e. Wien2k. The exchange correlation used for our study is Perdew Burke Ernzerhoff: Generalized Gradient Approximation (PBE-GGA). We have done electronic and optical investigation of the compound using the basic lattice parameters and other essential input parameters. The investigation has offered a bandgap of 1.005 eV which is suitable to quote for the optoelectronic applications. Optical properties like absorption, dielectric tensor (both real and imaginary), refraction and reflection have been investigated.